Rhetoric in Nursing - moh zainudin; windu santoso (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Rhetoric as a science is the art of speaking that is closely related to the science of nursing. In its application, rhetoric has five laws, namely inventio, dispositio, elocutio, memoria, and pronuntiatio. The correlation of rhetoric with nursing science is seen with the theory of caring in nursing, which is a theory that emphasizes a sense of concern for the client. The relationship between the nurse and the patient is determined by communication. Communication done by nurses to the patient is in need of rhetoric or art of talking, so the message delivered by the nurse can be well received by the patient.